First Complete Genome of the Thermophilic Polyhydroxyalkanoates-Producing Bacterium Schlegelella thermodepolymerans DSM 15344 - Musilova, Jana; Kourilova, Xenie; Bezdicek, Matej; Lengerova, Martina; Obruca, Stanislav; Skutkova, Helena; Sedlar, Karel (Genome biology and evolution, 2021)
Schlegelella thermodepolymerans is a moderately thermophilic bacterium capable of producing polyhydroxyalkanoates-biodegradable polymers representing an alternative to conventional plastics. Here, we present the first complete genome of the type strain S. thermodepolymerans DSM 15344 that was assembled by hybrid approach using both long (Oxford Nanopore) and short (Illumina) reads. The genome consists of a single 3,858,501-bp-long circular chromosome with GC content of 70.3%. Genome annotation identified 3,650 genes in total, whereas 3,598 open reading frames belonged to protein-coding genes. Functional annotation of the genome and division of genes into clusters of orthologous groups revealed a relatively high number of 1,013 genes with unknown function or unknown clusters of orthologous groups, which reflects the fact that only a little is known about thermophilic polyhydroxyalkanoates-producing bacteria on a genome level. On the other hand, 270 genes involved in energy conversion and production were detected. This group covers genes involved in catabolic processes, which suggests capability of S. thermodepolymerans DSM 15344 to utilize and biotechnologically convert various substrates such as lignocellulose-based saccharides, glycerol, or lipids. Based on the knowledge of its genome, it can be stated that S. thermodepolymerans DSM 15344 is a very interesting, metabolically versatile bacterium with great biotechnological potential.
Keywords: sekvenování celého genomu; sekvenční analýza DNA; genom bakteriální; Molecular Sequence Annotation; Whole Genome Sequencing; Sequence Analysis, DNA; zastoupení bazí; hybrid assembly; anotace sekvence; Base Composition; PHA; Genome, Bacterial; de novo assembly; functional annotation; Comamonadaceae